Medium Access Control Protocols for Wireless Body Area Networks: A Survey. (2016) - Sruthi, R.
Abstract: Wireless Body Area Networks (WBANs) consist of a number of miniaturized wearable or implanted sensor nodes that are employed to monitor vital parameters of a patient over long duration of time. For medical applications, these devices are placed or implanted inside the human body to measure and transfer the real time data or audio signals. Resource efficiency is one of the most important factors that should be considered when developing a MAC protocol in WBAN. There are different approaches used to design MAC protocols to minimize energy consumption. Here explains a comprehensive survey of recent medium access control (MAC) Protocols for wireless body area networks (WBANs). Finally, we suggested that hybrid protocol is more useful to achieve high energy efficiency.